Truck vibrations caused by unbalanced rotating shaft - Kučera, Pavel; Píštěk, Václav (JVE International, 2016)
This article presents an analysis of vibrations in drivetrain of an 8x8 truck caused by an unbalanced rotating drive shaft. This truck is also used in military and fire sphere. The aim was to reduce the vibrations affecting the drivers, therefore, a transient computational model for analysis of drivetrain shaft deflection was created in Matlab software. This model was compared to the simulation of the transient behaviour of a drivetrain shaft 3D model with the use of FEM. To verify the computational models, measurements of the rotating shaft deflection and directional oscillations on the truck driveline were carried out in the original version and then also with the designed modifications of the components. The conclusion presents the interpretation of the results.

This article presents an analysis of vibrations in drivetrain of an 8x8 truck caused by an unbalanced rotating drive shaft. This truck is also used in military and fire sphere. The aim was to reduce the vibrations affecting the drivers, therefore, a transient computational model for analysis of drivetrain shaft deflection was created in Matlab software. This model was compared to the simulation of the transient behaviour of a drivetrain shaft 3D model with the use of FEM. To verify the computational models, measurements of the rotating shaft deflection and directional oscillations on the truck driveline were carried out in the original version and then also with the designed modifications of the components. The conclusion presents the interpretation of the results.
Truck vibrations caused by unbalanced rotating shaft
Keywords: truck; drive shaft; vibration; driveline; Matlab; unbalance; FEM; truck; drive shaft; vibration; driveline; Matlab; unbalance; FEM